Basophils from allergy to cancer - Poto, Remo; Gambardella, Adriana Rosa; Marone, Gianni; Schroeder, John T.; Mattei, Fabrizio; Schiavoni, Giovanna; Varricchi, Gilda (Frontiers in Immunology, 2022)
Human basophils, first identified over 140 years ago, account for just 0.5-1% of circulating leukocytes. While this scarcity long hampered basophil studies, innovations during the past 30 years, beginning with their isolation and more recently in the development of mouse models, have markedly advanced our understanding of these cells. Although dissimilarities between human and mouse basophils persist, the overall findings highlight the growing importance of these cells in health and disease. Indeed, studies continue to support basophils as key participants in IgE-mediated reactions, where they infiltrate inflammatory lesions, release pro-inflammatory mediators (histamine, leukotriene C4: LTC4) and regulatory cytokines (IL-4, IL-13) central to the pathogenesis of allergic diseases. Studies now report basophils infiltrating various human cancers where they play diverse roles, either promoting or hampering tumorigenesis. Likewise, this activity bears remarkable similarity to the mounting evidence that basophils facilitate wound healing. In fact, both activities appear linked to the capacity of basophils to secrete IL-4/IL-13, with these cytokines polarizing macrophages toward the M2 phenotype. Basophils also secrete several angiogenic factors (vascular endothelial growth factor: VEGF-A, amphiregulin) consistent with these activities. In this review, we feature these newfound properties with the goal of unraveling the increasing importance of basophils in these diverse pathobiological processes.